The Manifestation Of Symbolic Violence In The Great Gatsby (2013): Pierre Bourdieu’s Perspective - Mensiana Tamo; Todo Sibuea (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
Symbolic violence is a gentle, imperceptible, and invisible violence that is often maintained by dominant groups through symbols, languages, cultures, and social norms. This study investigates the manifestation of symbolic violence in The Great Gatsby (2013) using Bourdieu’s theory of symbolic violence, focusing on concepts such as capital, habitus, field, and doxa. With a descriptive qualitative method and a multimodal critical discourse analysis approach, this study focuses on how symbolic violence is conveyed through various semiotic modes in the film, including verbal language, bodily gestures, visuals, and spatial arrangements. This study analyzes selected scenes that represent symbolic violence, focusing on six characters: Gatsby, Tom, Daisy, George, Myrtle, and Nick. The findings reveal that symbolic violence operates subtly through interactions shaped by social position and the unequal distribution of capital. Rather than being exercised by a single dominant character, symbolic violence emerges as a dynamic process where power shifts depending on who possesses dominant capital within specific social fields. These forms of symbolic violence are reinforced through the interplay of verbal, visual, gestural, and spatial elements of the film.